PERBEDAAN INTENSITAS KOMUNIKASI TIPE KEPRIBADIAN EXTROVERT DAN INTROVERT MELALUI MEDIA SOSIAL WHATSAPP DI INSTITUT AGAMA ISLAM SAHID BOGOR - Rijalul Fikri, Luthfy; El Raihan, Zulham (Fakultas Ilmu Dakwah dan Komunikasi, 2022)
The purpose of this research is to ascertain how intensely extroverted and introverted personalities communicate on social media platforms such as whatsapp. This research is qualitative research with two subjects and observation and in-depth interviews as data collection methods. The results showed that the two research subjects had different communication intensities, with subjects who had extroverted personalities having high communication intensity and often communicating through social media platforms to talk about everything they wanted to talk about, such as the content of daily activities. In addition, when speaking directly, they often talk about something the subject wants to talk about with other people. However, subjects with introverted personalities tend to prefer direct communication because they feel it is better to communicate directly, even though subjects with introverted personalities use the WhatsApp platform. They use social media to communicate in times of urgency or when they don't have time to meet and discuss things they want to talk about in person.